A study on the relationship of earning per share with capital structure, earning after tax and dividend payout ratio of construction companies / Harrison Para - Para, Harrison (2003)
This study examines the relationship of earning per share (EPS) with dividend payout ratio (DPR), common share (CS) and earning after tax (EAT) for the randomly selected public listed construction companies at Kuala Lumpur Stock Exchange (KLSE) main board for the period of 1996 to 2000. General analysis and statistical analysis have been done to the compiling annual data. In order to obtain a multiple regression analysis, hypothesis testing and correlation analysis, a Statistical Programme Software System (SPPS) is used. The results show that, there is a positive relationship between EPS and EAT. However, there is less significant relationship between EPS with DPR and CS, meaning that when there is a changes in DPR or CS they will not necessarily affect the company EPS. From the study, we can conclude that the variation or changes in EPS were also influenced by other factors beside DPR, CS and EAT. Efficient managers and adoption of better corporate governance contribute to the success of the company regardless of any economic situation.